Regulation of glucose metabolism in bovine embryos - De La Torre Sanchez, Jose Fernando, author; Seidel, George E., Jr., advisor; Anthony, Russell, committee member; Burns, Patrick, committee member; Graham, James, committee member (Colorado State University. Libraries, 2004)
The objective of this research was to evaluate glucose metabolism and other characteristics of bovine embryos treated with molecules that regulate carbohydrate metabolism to improve normality of embryos produced in vitro. A preliminary experiment compared in vitro development of embryos exposed to four levels of phosphate (1250, 250, 50 and 0 μM) and three levels of citrate (500, 50 and 0 μM) in a chemically defined media system (CDM1/CDM2) plus fatty acid-free BSA. A phosphate x citrate interaction for lightness-darkness (dark= more lipids) of embryos at 36 h (P<0.04) was found. Citrate decreased embryo lipid accumulation (darkness) in the presence of the highest concentration of phosphate compared to other treatments. Four experiments were then done to evaluate the toxicity/beneficial effects of four regulators of glucose metabolism on development of embryos. Phenazine ethosulfate (PES), phloretin (PL), pyrroline-5-carboxylate (P5C), and sodium azide (NaN3) were included at four doses (0, 0.1, 0.3, and 0.9 μM; 0, 30, 90, and 270 μM; 0, 9, 27, and 81 μM; and 0, 3, 9, and 27 μM, respectively) in factorial combination with glucose concentrations of 0, 0.5, 2 and 8 mM. Compact morulae produced in vitro using the CDM1/CDM2 culture system were allocated to treatments (~5760 total morulae), and evaluated blindly after 36 and 72 h for stage of development, morphological quality, lightness-darkness, inner cell mass quality, percentage of blastocysts, and number of cells. The highest PES dose evaluated (0.9 μM) resulted in poorer development than treatments with lower doses (P<0.05). Presence of PL was detrimental for many of the responses studied, especially for the two highest doses. P5C had little effect on post-compaction embryos at any dose. Inclusion of 27 μM NaN3 in culture medium resulted in lighter embryos at 72 h compared to lower or no NaN3 (P<0.01). There was little effect of NaN3 on quality of embryos except the higher NaN3 levels resulted in more advanced and better quality embryos at 36 h of culture, when cultured in 2 mM glucose, but not at other concentrations. The dose-response information obtained for these four regulatory molecules was used to choose effective but non toxic doses for later experiments. Two more screening experiments were completed with 2, 4-dinitrophenol (DNP). First, embryos were produced with the CDM1/CDM2 system, and allocated to treatments at the 8- to 16-cell stages. Three doses of DNP (10, 30, and 90 μM), and three times of exposure (early, late and both) were evaluated. A tenth treatment was no DNP (control). Embryos cultured in 90 μM DNP developed slower and were darker than embryos cultured at lower doses. When compared to the control, 30 μM DNP-treated embryos had a higher blastocysts rate. DNP in early culture resulted in more advanced and lighter embryos than in late culture. The second experiment was done in the G1/G2 chemically defined system, using 30 μM DNP at different developmental stages. With this system DNP was detrimental when embryos were exposed at early cleavage stages, but had little effect on embryo development with exposure at later stages. Two experiments were done to compare in vivo versus in vitro-produced embryos at two developmental stages, and to evaluate how changing development conditions (vivo to vitro and vice versa) at the compaction stage affects blastocyst development. Day 5 and day 7 embryos were produced in vitro, and obtained in vivo with the G1/G2 system. In the second experiment, day-7.5 embryos were produced in four different ways: vitro-vivo (VT-VI); embryos were produced in vitro with the G1/G2 system; on day five embryos were transferred to recipient cows, and recovered 2 1/2 days later. Vivo vitro (VIVT): In vivo embryos were collected at day 5, and then placed in culture in G-2 for 2 1/2 days. Vitro-Vitro (VT-VT): Day-7.5 embryos were produced completely in vitro in G1/G2. Vivo-Vivo (VI-VI): day-5 in vivo embryos were recovered, transferred to a recipient cow, and 2 1/2 days later embryos were recovered from recipients. In the first experiment Day-7 vitro (D7VT) embryos metabolized more glucose than Day-5 vitro embryos (D5VT) (P<0.06); also, the two groups of day-7 embryos had more cells than their day-5 counterparts (P<0.1). The D7VT group had more medium and large lipid granules, when compared to D7VI (P<0.1), and to D5VT (P<0.1). In experiment 2, VT-VI and VI-VT embryos metabolized less glucose than VI-VI and VT-VT embryos (10.7±1.6 and 9.0±4.5 vs 15.4±1.7 and 19.3±2.0, respectively, P<0.1). Embryos produced completely in vitro (VT-VT) had higher lactate production than embryos produced in vivo (VI-VI) (P<0.6). No other differences were detected in metabolic parameters and numbers of cells per embryo among the treatments. Embryos graded as good metabolized more glucose (16.6±1.18 pMol/embryo/h) than those graded fair (10.6±2.48 pMol/embryo/h) (P<0.5). This effect was most pronounced on VT-VT group (P<0.05 for quality x group interaction). Amounts of glucose metabolized were similar among embryos produced completely in vivo versus in vitro, but were lower in VI-VT and VT-VI groups (P<0.05). In vitro-produced embryos had higher lactate production than in vivo embryos. In the last experiment, we compared effects of three metabolic regulators added to G2 medium during compaction and blastulation stages of in vitro-produced bovine embryos. Eight- and 16-cell embryos were randomly allocated to the following treatments: PES, 0.3 μM; NaN3, 27 μM; DNP, 30 μM; and control, no metabolic regulator. Forty to 50 8- to 16-cell embryos were allocated per treatment per replicate, resulting in 10-15 normal seven-day embryos for evaluation. Radiolabeled glucose was used to study glucose metabolism and pentose phosphate pathway (PPP) rates. Glucose uptake and lactate production was determined by microfluorometry. For lipid quantification, embryos were fixed and stained with Sudan Black B, and lipid granules were quantified microscopically. In four replicates, embryos were transferred to synchronized recipients, and recovered seven days later for evaluation. No differences were found among treatments in blastocyst rate, stage, quality and lightness; average blastocyst production from 8- to 16-cell embryos was 40.3%. PES-treated embryos had the highest glucose metabolism, 18.5 pMol/embryo/h (P<0.5 compared to NaN3) and tended to have a higher PPP rate (P<0.12) than controls (50.5% vs 22.1); however, glucose uptake was lower (13.1 pMol/embryo/h) and glycolysis was higher with PES than other treatments (187.3%) (P<0.1). Lipid accumulation of embryos from PES was markedly lower than any other in vitro treatment (P<0.1), but still higher than in vivo embryos from the previous experiment (P<0.1). NaN3-treated embryos metabolized the least glucose (11.1 pMol/embryo/h, P<0.05), but had highest glucose uptake (38.9 pMol/embryo/h). Lipid accumulation was high in this treatment. DNP-derived embryos had intermediate values in all the metabolic parameters studied, and also were characterized by accumulation of lipids similar to controls. No treatment differences were found in developmental competence when day-7 embryos were transferred to recipients and recovered 1 week later (average 48.6% of recovery of live embryos). The most important conclusion from this research is that 0.3 μM PES resulted in in vitro production of embryos that were more similar to in vivo-produced embryos than controls with respect to amounts of cytoplasmic lipid.
Keywords: anatomy and physiology; animals; animal diseases